Dor lombar, quedas e autoeficácia em evitar quedas em idosos comunitários: follow-up de um ano do estudo back complaints in the elders (bace – brasil) - Juliana Lima Fonteles Magalhães (2019)
Low back pain (LBP), a musculoskeletal condition prevalent in the elders, may be associated with functional disability, a factor that may cause the elders individual to fall. Falls are the main cause of morbidity and mortality in this population, and studies related to the multifactorial causes that lead the elders with LBP to fall are still scarce and should be conducted. The general objective of this thesis was to verify the variables related to LBP and its association with falls and self-efficacy in avoiding them after a year of follow-up using data from the international multicenter study Back Complaints in the Elders (BACE-Brazil). Two articles were produced from this thesis. The first one titled Low back pain and self-efficacy in avoiding falls in the community elders: a prospective cohort study (BACE-Brazil) had as objective to verify association between intensity and disability caused by the LBP with the auto efficacy in avoiding fall, using a subsample of 578 participants with 60 years or more at baseline, 6 and 12 months. Self-efficacy, pain intensity and LBP disability were measured by the Falls Efficacy Scale (FES-I), Numerical Rating Scale (NRS) and Rolland Morris Disability Questionarie (RMDQ) respectively. Models of Generalized Estimating Equations (GEE) were generated to evaluate the longitudinal associations with adjustments for the potential confounding variables. The mean age was 67.6 years (SD ± 7), composed mostly of females (84.8%), with income of up to one minimum wage (40.4%) and low schooling (62.3% %). GEE regression analysis, including socio-demographic and clinical variables, identified a significant interaction between pain intensity and FES-I categories. Elders patients with severe NRS pain were less effective (FES-I ≥ 23) in avoiding falls (OR 1.86 95% CI 1.21-2.86, p = 0.005) than the reference category. Low self-efficacy was also associated with disability (RMDQ> 14) (OR 4.46 95% CI 2.98 - 6.66, p <0.001). The female sex (OR 2.42 95% CI 1.57 - 3.74, p <0.001) and the presence of more than two comorbidities (OR 1.92 95% CI 1.30-2.86, p = 0.001) also increased the chance of outcome. The article 2 titled Falls in the elders with acute low back pain: incidence and risk factors associated after one year of follow-up of the Back Complaints in the Elders Study (BACE-BRAZIL) used baseline measures six and 12 months after the initial assessment to describe the incidence of falls after one year of follow-up, as well as to verify the risk factors associated with the event. Self-efficacy, pain intensity and LBP disability were measured by the same instruments of the first article. The presence of depressive symptoms and comorbidities were measured by the Center for Epidemiological Scale-Depression (CES-D) and Self-administered Comorbidity Questionnaire (SCQ) respectively. The usual walking speed was also measured in meters per second. Of the 602 Brazilian elders in the total sample of Brazil, 156 (26%) reported episodes of baseline falls in the last six weeks prior to the initial evaluation and were excluded for the determination of risk factors after one year in this study. Of the 446 elderly people included in the analyzes, 375 (84%) were women, and of these 112 (79.43%) reported at least one episode of falls after one year of follow-up. The socio-demographic characteristics that were associated with falls were: female gender (p = 0.068), age (p = 0.004) and low level of schooling (p = 0.022). In the analysis of the continuous data, falling elders presented higher levels of pain intensity at 12 months (p <0.001) and disability at 6 months and 12 months (p = 0.017 and p = 0.037), respectively, revealing that falling elders had higher levels of disability due to pain. The self-efficacy to prevent falls after 12 months was different between the groups of falling and non-falling elders (p = 0.003) with higher scores for those reporting falls indicating low self-efficacy. The gait velocity did not differ significantly between the elderly who fell or did not fall after one year (p = 0.861). The regression analyzes identified that although these variables were associated with the falls, they were not risk factors for the falls as an outcome in the elders of this sample. Therefore, the results from this thesis indicate that elderly people with a greater intensity of low back pain and disability for low back pain have a lower selfefficacy to avoid falls and that these same variables are associated with the presence of falls after one year of follow-up in the elders with low back pain. However, they are not risk factors for the outcome, in this sample. Thus, it is necessary to develop more longitudinal studies that address the multifactorial aspects related to falls in special populations.